THE IMPACT OF HUMANIZATION AND DEMOCRATICIZATION OF EDUCATION IN UZBEKISTAN ON THE CREATIVE ACTIVITY OF YOUTH - Makhmanazarov Kahramon Abdiyevich (Journals Park Publishing, 2025)
This scientific article analyzes the impact of the processes of humanization and democratization of the education system in the Republic of Uzbekistan on the creative activity of young people. The study examines the role of individual-oriented models of education based on modern pedagogical approaches, the introduction of democratic principles and their importance in developing the creative potential of young people. The article presents analytical materials on educational reforms being implemented in Uzbekistan, innovative methods combined with national values, as well as the effectiveness of spiritual and educational work.
Keywords: Humanization of education, democratization of education, creative activity, youth education, pedagogical reforms, spiritual and educational work, person-centered education, education system of Uzbekistan.